Investigation of Machine Learning Techniques for Fault Diagnosis in the Semiconductor Manufacturing Process - Nuhu, Abubakar Abdussalam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Industries are going through the fourth industrial revolution (Industry 4.0), where technologies like the Industrial Internet of Things (IIoT), Big Data Analytics and Machine Learning (ML) are being extensively employed for improving the productivity and efficiency of manufacturing systems. Recently, many researchers have demonstrated the ability of ML algorithms to meet various challenges presented by the next generation Smart Manufacturing Systems (SMSs). This work aims to investigate the applicability of several machine learning techniques for early fault diagnosis towards smart manufacturing process. Thus, in this thesis, we propose several fault diagnosis ML models for SMSs applications. A case study has been conducted on a dataset from a semiconductor manufacturing process. However, this dataset contains missing values, redundant and noisy features, and class imbalance problem. This imbalance problem makes it so difficult to accurately predict the minority class, due to the majority class size difference. Therefore, this work proposes and compares the effects of three synthetic data generation techniques to handle such class imbalance problem. To handle issues related to missing values and redundant features, we implemented and compared the performance of two missing values imputation techniques and two feature selection techniques using three adopted data synthetic generation techniques. We then developed and compared the performance of ten predictive machine learning models against the abovementioned proposed approaches. Experimental results across seven evaluation metrics of performance obtained from these models were significant. These results and a comparative analysis show the feasibility and validate the effectiveness of these proposed synthetic data generation techniques and the proposed methodologies. Some among the proposed methodologies could produce an accuracy in the range of 99.9% to 100%. Furthermore, a comparative analysis has been conducted with similar models proposed in the literature. Based on the results, our proposed models outpace those proposed in the literature.

ÖZ: Endüstriler, Endüstriyel Nesnelerin İnterneti (IIoT), Büyük Veri Analitiği ve Makine Öğrenimi (ML) gibi teknolojilerin üretim sistemlerinin üretkenliğini ve verimliliğini artırmak için yoğun bir şekilde kullanıldığı dördüncü endüstriyel devrimden (Endüstri 4.0) geçiyor. Son zamanlarda, birçok araştırmacı, ML algoritmalarının yeni nesil Akıllı Üretim Sistemleri (SMS'ler) tarafından sunulan çeşitli zorlukları karşılama becerisini göstermiştir. Bu çalışma, akıllı üretim sürecine yönelik erken arıza teşhisi için çeşitli makine öğrenme tekniklerinin uygulanabilirliğini araştırmayı amaçlamaktadır. Bu nedenle, bu tezde, SMS uygulamaları için çeşitli arıza teşhis ML modelleri öneriyoruz. Yarı iletken üretim sürecinden bir veri seti üzerinde bir vaka çalışması yapılmıştır. Bununla birlikte, bu veri kümesi eksik değerler, fazlalık ve gürültülü özellikler ve sınıf dengesizliği problemini içermektedir. Bu dengesizlik sorunu, çoğunluk sınıf büyüklüğü farkı nedeniyle azınlık sınıfını doğru bir şekilde tahmin etmeyi çok zorlaştırıyor. Bu nedenle, bu çalışma, bu tür bir sınıf dengesizliği sorununu ele almak için üç sentetik veri oluşturma tekniğinin etkilerini önermekte ve karşılaştırmaktadır. Eksik değerler ve gereksiz özelliklerle ilgili sorunları ele almak için, benimsenmiş üç veri sentetik oluşturma tekniğini kullanarak iki eksik değer atama tekniğinin ve iki özellik seçim tekniğinin performansını uygulayıp karşılaştırdık. Daha sonra on tahmine dayalı makine öğrenimi modelinin performansını yukarıda belirtilen önerilen yaklaşımlarla geliştirip karşılaştırdık. Bu modellerden elde edilen performansın yedi değerlendirme metriğine ilişkin deneysel sonuçlar anlamlıydı. Bu sonuçlar ve karşılaştırmalı bir analiz, bu önerilen sentetik veri oluşturma tekniklerinin ve önerilen metodolojilerin uygulanabilirliğini gösterir ve etkililiğini doğrular. Önerilen metodolojilerden bazıları, % 99,9 ila% 100 aralığında bir doğruluk sağlayabilir. Ayrıca, literatürde önerilen benzer modellerle karşılaştırmalı bir analiz yapılmıştır. Sonuçlara göre, önerilen modellerimiz literatürde önerilenleri geride bırakıyor
Master of Science in Mechanical Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2021. Supervisor: Assoc. Prof. Dr. Qasim Zeeshan
Keywords: Mechanical engineering Department; Smart Manufacturing Systems--Machine Learning; Production management; Computer-aided engineering; Semiconductor Manufacturing Process, Fault Diagnosis, Imbalance Dataset, Synthetic Data Generation, Machine Learning.